Предмет: Алгебра,
автор: ladyFilimonova
решить уравнение:
1) 6х-(2х+5)=2(3х-6)
2) х(х-4)=(х+3)²
Ответы
Автор ответа:
0
6х+2х-5=6х-12
6х+2х-6х=5-12
2х=-7
х=-7/2
х=-3,5
6х+2х-6х=5-12
2х=-7
х=-7/2
х=-3,5
Автор ответа:
1
1)6х-2х-5=6х-12;
4х-6х=5-12;
-2х=-7;
х=3,5
2) х^2-4х=х^2+6x+9;
x^2-x^2-4x-6x-9=0;
-10x-9=0;
-10x=9;
x=-0,9
4х-6х=5-12;
-2х=-7;
х=3,5
2) х^2-4х=х^2+6x+9;
x^2-x^2-4x-6x-9=0;
-10x-9=0;
-10x=9;
x=-0,9
Похожие вопросы
Предмет: Українська мова,
автор: Besj
Предмет: Русский язык,
автор: Sedova2006vika
Предмет: Қазақ тiлi,
автор: Kamalzhanovaa05
Предмет: История,
автор: Permarganat
Предмет: Алгебра,
автор: Влад6061